Thermal Comfort in High-rise Urban Environments in Singapore. (2015) - Yang, Wei; Wong, Nyuk Hien; Lin, Yaolin
Abstract: Outdoor thermal comfort in urban spaces is an important indicator of the quality of life in urban environment. This paper attempts to investigate outdoor thermal comfort in an urban street surrounded by high-rise commercial buildings in the central business district in Singapore, focusing on the effect of height-to-width ratio (H/W) on outdoor thermal comfort. The microclimatic parameters of different H/W scenarios were determined by ENVI-met numerical simulation. Field measurement was conducted to validate the results from the numerical simulation and they were in good agreement. The physiologically equivalent temperature (PET) was utilized as the thermal index to assess outdoor thermal comfort. It has been approved quantitatively that shading provided by high aspect ratios can improve outdoor thermal comfort in urban streets and H/W of 3 can be considered as a threshold with respect to outdoor thermal comfort in Singapore.